ASPEK HUKUM PIDANA DALAM KAITANNYA DENGAN PERIZINAN DI BIDANG PERTAMBANGAN - Oheo K.Haris (Universitas Airlangga, 2014)
Formulation of maladministration is confounding between a fault, an official responsibility or a personal responsibility. The definition of maladministration in the criminal provisions on the Act 4 of 2009, the formulation of Article 165 does not specify fault elements as well as the intent and dolus and culpa relating to criminal liability. In addition, the criminal provisions on the Act No. 4 of 2009 has not memprekripsikan of malversation as a whole, only contains a clause of Article 165. In many cases related to the regional head of mining permits in some areas, so many overlapping permits caused by maladministration authoritie.Keywords: maladministration, responsibilities, permissions.